2008
DOI: 10.1056/nejmoa060781
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Athletes with Marked ECG Repolarization Abnormalities

Abstract: Markedly abnormal ECGs in young and apparently healthy athletes may represent the initial expression of underlying cardiomyopathies that may not be evident until many years later and that may ultimately be associated with adverse outcomes. Athletes with such ECG patterns merit continued clinical surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
152
1
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 264 publications
(168 citation statements)
references
References 30 publications
5
152
1
10
Order By: Relevance
“…16 Our results reaffirm that marked PTWI is associated with a high prevalence of cardiac pathologies that are associated with conditions that may predispose athletes to SCD. 9 Although our prevalence of disease is slightly higher than previously reported (45% versus 36%), 9 in keeping with the majority of studies, HCM was our most common identified pathology (81% of all cases). Accordingly, all athletes with disease were excluded from competitive sports as recommended.…”
Section: Prevalence Of Cardiac Disease In Athletes Presenting With Ptwicontrasting
confidence: 41%
See 1 more Smart Citation
“…16 Our results reaffirm that marked PTWI is associated with a high prevalence of cardiac pathologies that are associated with conditions that may predispose athletes to SCD. 9 Although our prevalence of disease is slightly higher than previously reported (45% versus 36%), 9 in keeping with the majority of studies, HCM was our most common identified pathology (81% of all cases). Accordingly, all athletes with disease were excluded from competitive sports as recommended.…”
Section: Prevalence Of Cardiac Disease In Athletes Presenting With Ptwicontrasting
confidence: 41%
“…9 Our data demonstrate the importance of annual follow-up, because almost 6% athletes who presented with PTWI but normal secondary investigations in initial examination later went onto develop clear pathology during follow-up.…”
Section: Importance Of Annual Cardiovascular Follow-upmentioning
confidence: 99%
“…Early repolarization was noted in about one-third of the athletes, and LVH together with early repolarization occurred in 22% of the players. No evidence of deeply inverted T-waves suggestive of increased risk for cardiomyopathy 6 were found in any of our football athletes. None of the athletes showed evidence of significant atrial ectopy other than mild sinus arrhythmia, nor was there evidence of ventricular ectopy, bundle branch block, or second-degree or thirddegree AV block.…”
Section: Resultsmentioning
confidence: 49%
“…2,4 In contrast to this conclusion, recent evidence from a large pool of athletes in various sports suggests that deeply inverted T-waves (≥2 mm) in at least 3 ECG leads may be predictive of serious, later-developing cardiomyopathies. 6 None of our football athletes showed this potentially serious abnormality. In light of the high frequency of abnormal resting ECG findings in our study, it is noteworthy that all maximal treadmill exercise stress tests were completed by the athletes without cardiovascular incident, and evaluated as normal with no evidence of ischemia or arrhythmias.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation